Auxiliary Power Supply System with Parallel-Connected DC–AC Inverters for Low-Floor Light Rail Vehicle - Paiwan Kerdtuad; Kunjana Chaiamarit; Supat Kittiratsatcha (Electronics, 2023)
This research proposes a roof-mounted auxiliary power supply (APS) system for 600 VDC low-floor light rail vehicles (LRVs). The proposed APS system consists of five parallel-connected dc–ac inverter modules (modules 1–5). Inverter modules 1 and 2 are three-phase dc–ac inverters for the compressor motors of the air conditioning system, and inverter modules 3 and 4 are three-phase dc–ac inverters for the air pump motors of the air supply system. Inverter module 5 is a single-phase dc–ac inverter for the 220 VAC power supply of onboard electric loads. Simulations and experiments were carried out under variable load torques and output frequencies for modules 1–4 and under full and no resistive loads for module 5. The measured total input current and total input power of the proposed APS system under the full-load condition are 114.36 A and 68.84 kW. The total efficiency of the proposed APS system (modules 1–5) is 97.05%. The proposed APS system is suitable for 600 VDC low-floor LRVs. The novelty of this research lies in the use of five parallel-connected inverter modules, as opposed to the three-phase output transformer or isolated dc–dc converter in the early and conventional APS systems. Specifically, the proposed APS system requires neither a three-phase output transformer nor an isolated dc–dc converter.
Keywords: Railway Systems and Energy Efficiency; Electric and Hybrid Vehicle Technologies; Electrical Contact Performance and Analysis